Standards and Agro-Food Exports from Developing Countries: Rebalancing the Debate - Jaffee, Steven; Henson, Spencer (World Bank, Washington, D.C., 2013)
The proliferation and increased stringency of food safety and agricultural health standards is a source of concern among many developing countries. These standards are perceived as a barrier to the continued success of their exports of high-value agro-food products (including fish, horticultural, and other products), either because these countries lack the technical and administrative capacities needed for compliance or because these standards can be applied in a discriminatory or protectionist manner. The authors draw on available literature and work in progress to examine the underlying evidence related to the changing standards environment and its impact on existing and potential developing country exporters of high-value agricultural and food products. The evidence the authors present, while only partial, suggests that the picture for developing countries as a whole is not necessarily problematic and certainly less pessimistic than the mainstream "standards-as-barriers" perspective. Indeed, rising standards serve to accentuate underlying supply chain strengths and weaknesses and thus impact differently on the competitive position of individual countries and distinct market participants. Some countries and industries are even using high quality and safety standards to successfully (re-)position themselves in competitive global markets. This emphasizes the importance of considering the effects of food safety and agricultural health measures within the context of wider capacity constraints and underlying supply chain trends and drivers. The key question for developing countries is how to exploit their strengths and overcome their weaknesses such that they are gainers rather than losers in the emerging commercial and regulatory context.